2000
DOI: 10.1001/archneur.57.12.1761
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Embolism to the Basilar Apex Associated With May-Thurner Syndrome

Abstract: Deep venous thrombosis is notorious for its variable clinical manifestations and the potential dire consequences of a missed diagnosis. Physicians caring for patients with presumed paradoxical embolism should assess for May-Thurner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Although the association between MTS and cryptogenic stroke was previously reported in case reports (3, 4), the current study is the first large-scale analysis of the association between MTS, cryptogenic stroke and PFO. In our study we found an incidence of MTS of 6.3% in patients diagnosed with cryptogenic stroke having undergone PFO closure.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although the association between MTS and cryptogenic stroke was previously reported in case reports (3, 4), the current study is the first large-scale analysis of the association between MTS, cryptogenic stroke and PFO. In our study we found an incidence of MTS of 6.3% in patients diagnosed with cryptogenic stroke having undergone PFO closure.…”
Section: Discussionmentioning
confidence: 71%
“…Apart from case reports (3, 4), the association of MTS with cryptogenic stroke in the context of a patent foramen ovale (PFO) has not been studied. The incidence of MTS in patients with cryptogenic stroke and PFO is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral emboli have been reported to account for approximately 15% of all ischemic strokes [1]. ASDs and PFOs are congenital cardiac defects that have been associated with paradoxical cryptogenic ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…MTS consists of venous flow impedance of the left common iliac vein by the overlying right common iliac artery, which may lead to intimal hypertrophy, further flow impedance, and thrombus formation secondary to chronic pulsatile forces. MTS has been estimated to occur in 20% of the population and the average age of onset is between 18 and 30 years of age and is approximately five times more common in women than men [1,3-6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation